2021
DOI: 10.3389/fphys.2021.681011
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte Deletion of Bmal1 Exacerbates QT- and RR-Interval Prolongation in Scn5a+/ΔKPQ Mice

Abstract: Circadian rhythms are generated by cell autonomous circadian clocks that perform a ubiquitous cellular time-keeping function and cell type-specific functions important for normal physiology. Studies show inducing the deletion of the core circadian clock transcription factor Bmal1 in adult mouse cardiomyocytes disrupts cardiac circadian clock function, cardiac ion channel expression, slows heart rate, and prolongs the QT-interval at slow heart rates. This study determined how inducing the deletion of Bmal1 in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…The different types of transgenic mice used in these studies include the germline Bmal1 knockout (Bmal1 -/-) mice (Bunger et al, 2000), the cardiomyocyte-specific Bmal1 knockout (CBK) mice (Young et al, 2014) and mice that allow for inducing the cardiomyocyte-specific deletion of Bmal1 (iCS Bmal1) in adult mouse hearts (Schroder et al, 2013). Data from these studies show that the circadian oscillation in Kcnip2 mRNA transcript levels were reduced in Bmal1 -/mice, and the circadian oscillation and mRNA transcript levels in Kcnh2, Kcnq1, Kcnj2, Hcn4 and Scn5a mRNA were lost and reduced in iCS Bmal1 mice after inducing the deletion of Bmal1 (iCS Bmal1 -/-) (Jeyaraj et al, 2012;Schroder et al, 2013Schroder et al, , 2015Schroder, Wayland et al, 2021). These studies confirmed that the core circadian clock mechanism in cardiomyocytes regulates cellular ion channel mRNA levels.…”
Section: Cardiomyocyte Circadian Clocks Regulate Cardiac Ion Channel ...mentioning
confidence: 99%
See 3 more Smart Citations
“…The different types of transgenic mice used in these studies include the germline Bmal1 knockout (Bmal1 -/-) mice (Bunger et al, 2000), the cardiomyocyte-specific Bmal1 knockout (CBK) mice (Young et al, 2014) and mice that allow for inducing the cardiomyocyte-specific deletion of Bmal1 (iCS Bmal1) in adult mouse hearts (Schroder et al, 2013). Data from these studies show that the circadian oscillation in Kcnip2 mRNA transcript levels were reduced in Bmal1 -/mice, and the circadian oscillation and mRNA transcript levels in Kcnh2, Kcnq1, Kcnj2, Hcn4 and Scn5a mRNA were lost and reduced in iCS Bmal1 mice after inducing the deletion of Bmal1 (iCS Bmal1 -/-) (Jeyaraj et al, 2012;Schroder et al, 2013Schroder et al, , 2015Schroder, Wayland et al, 2021). These studies confirmed that the core circadian clock mechanism in cardiomyocytes regulates cellular ion channel mRNA levels.…”
Section: Cardiomyocyte Circadian Clocks Regulate Cardiac Ion Channel ...mentioning
confidence: 99%
“…The studies found that, in mouse hearts, the mRNA transcript levels for Kcnd2, Kcnip2, Kcnh2, Kcnq1, Kcnj2, Hcn4 and Scn5a cycled with a periodicity of 24 h in free-running conditions (Fig. 2A) (Jeyaraj et al, 2012;Schroder et al, 2013Schroder et al, , 2015Schroder, Wayland et al, 2021;Zhang et al, 2014). To investigate the role that the cardiomyocyte circadian clock has on the transcriptional regulation of these ion channels, the circadian oscillation in mRNA transcript levels was studied using transgenic mouse models that disrupt cardiomyocyte circadian clock signalling by Bmal1 knockout or deletion.…”
Section: Cardiomyocyte Circadian Clocks Regulate Cardiac Ion Channel ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The differentiallyexpressed genes (significantly downregulated genes) involved in ion channels by Bmal1 knockdown were KCNJ14, KCNJ6, and CAMK2B. Bmal1 has been shown to modulate cardiac 10.3389/fcvm.2022.937608 ion channel transcription by binding to the enhancer box (Ebox) elements in the promoters of these genes or altering the expression of other transcription factors that regulate ion channel transcription (24). The differentially-expressed genes involved in receptors for transmitters upregulated by Bmal1 knockdown were GABBR2, GABRE, GABRG1, GABRQ, and HTR5A; and the genes downregulated were DRD2.…”
Section: Bmal1 Modulates the Expression Of Genes Associated With Neur...mentioning
confidence: 99%